Analysis of Final-Year Student Stress Levels Using the Simple Additive Weighting (SAW) Method - Hanti Prihatini; Feri Alpiyasin (Journal of Multimedia Technology and Applied Software, 2026)
Final year students often face increasing academic pressure along with the demands of completing final assignments and graduation targets. This pressure has the potential to cause stress that impacts students' psychological condition and academic achievement. This study aims to identify the stress levels of final year students by utilizing a Decision Support System based on the Simple Additive Weighting (SAW) method. Research data were obtained through a questionnaire compiled based on several academic and non-academic criteria. The obtained values were then processed using the SAW method stages to produce preference values that are used as the basis for classifying stress levels into low, medium, and high categories. The results showed that the majority of students were in the moderate stress category. These findings are expected to provide an objective picture of the stress conditions of final year students and become a consideration in developing academic mentoring strategies. Keywords: Decision Support System; Simple Additive Weighting; Stress Levels